Opportunities and Challenges in the Development of A Sustainable Capital City of Nusantara (Jurnal Lemhannas RI, 2024)
Purpose: The sustainable development of Nusantara, Indonesia's new capital city, under Law No. 3 of 2022 requires a robust commitment from the central government, supported by all elements of society. The relocation of the capital from Jakarta to Nusantara brings forth numerous challenges that demand comprehensive mitigation strategies, especially in uniting local and newcomer communities to collaborate effectively in building IKN Nusantara, ensuring inclusivity and shared progress.Study Design/Methodology/Approach: This study employs a descriptive research design, utilizing SWOT Analysis to examine the opportunities and challenges in achieving sustainable development in IKN Nusantara. Narrative data analysis is applied to interpret the findings in line with the research objectives.Findings: The study identifies several opportunities for the sustainable development of IKN Nusantara, including policy formulation, investment opportunities from domestic and international sources, optimization of State Property (BMN), and development of the metropolitan region "Nusamba Bojaserakarta" as a support area. Additionally, opportunities for interregional cooperation, enhancing national connectivity, and population mobility were highlighted. However, significant challenges exist, including the need for development plans that align with natural conditions, the integration of national values, and the achievement of low-carbon emissions targets.Originality/Value: This research offers valuable insights into the strategic planning and potential obstacles in the development of Indonesia’s new capital. It provides a balanced perspective on how opportunities can be maximized while addressing critical challenges to ensure the long-term sustainability of IKN Nusantara
Keywords: Sustainable of IKN; Smart Cities; Symbol of National Identity